Konstytucja Japonii z 1946 roku – droga i proces ustrojodawczy - Piegzik, Michał A. (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The main aim of this paper is to present the legislation process and background of the Japanese Constitution of 1946. At the end of World War II in the Pacific the Empire of Japan was submitted under the military occupation of the United States. The defeated country, responsible for the aggression of the vast territories of East Asia, was expected never to return to the aggressive policy in the international arena. The most important priorities of the American occupation headquarters, whose main representative was General Douglas MacArthur, was to the change the socio-economic system of Japan, taking into account the specific nature of the Japanese nation. The Meiji Constitution was considered the main core of Japanese political life, which according to the Americans was far from democratic standards. In order to adopt a new constitution MacArthur engaged Japanese politicians, who formed different groups working on its draft. Already at the end of 1945 the cabinet created the so-called Matsumoto Committee composed of eminent Japanese lawyers, which became the main center of the work on a new constitution. The differences in the Japanese and American visions of the future constitution of Japan led to many meetings and negotiations, in which the interpretation of the concept of sovereignty and the role of the emperor was discussed. Forming their own constitutional committee the Americans created their project of the constitution for Japan, which put the emphasis on democratization and liberalization of the state. After several meetings with the representatives of the American office the project was partially revised at the request of Japanese politicians, retaining its original character. Finally, in June 1946 the legislative process began in the Japanese Diet which ended with the adoption of a new constitution on the 6th of October. The Constitution was subsequently promulgated by the Emperor and significantly changed the socio-economic structure of a country which took the democratic path.
Keywords: Japan; Matsumoto Committee; Constitution of Japan; Occupation of Japan after World War II